The impact of adjuvant chemotherapy on overall survival and cancer-specific survival in patients with extrahepatic cholangiocarcinoma across different age groups: a population-based study - Liu, Tingyu; Liu, Chang; Ren, Hefei; Zhou, Lin (Journal of Gastrointestinal Oncology, 2026)
Background: Extrahepatic cholangiocarcinoma (ECC) has a high postoperative recurrence rate, and the value of adjuvant chemotherapy (AC) by age remains unclear. This study investigated the influence of AC on long-term survival in patients with ECC, with analysis stratified by age.Methods: Patient data were extracted from the Surveillance, Epidemiology, and End Results (SEER) database for individuals diagnosed with ECC from 2010 to 2020. Kaplan-Meier (KM) analysis evaluated the association between AC and long-term survival across age strata. Subsequently, univariate and multivariate Cox regression analyses were performed to analyze the overall survival (OS) and cancer-specific survival (CSS) of ECC patients across different age groups. Furthermore, propensity score matching (PSM) was used to reduce the potential selection bias. Lastly, sensitivity analysis was conducted to assess the robustness of the results.Results: This study included 2,189 patients with ECC, who were divided into four groups according to age: 18–55, 56–65, 66–75 and 76–85 years old. Before PSM adjustment, no statistically significant association was observed between AC and long-term survival in the 18–55 and 56–65 years age groups. In contrast, significant differences in long-term survival were observed in patients aged 66–75 years. For those aged 76–85 years, only OS showed a significant difference. Following adjustment, the absence of significant differences persisted in the two younger age groups. Statistically significant differences in long-term survival, however, were maintained in both the 66–75 and 76–85 years age groups. Multivariate Cox regression analysis demonstrated that patients in the 18–55 and 56–65 years age groups did not benefit from AC. In the 66–75 years age group, AC acted as an independent protective factor. In the 76–85 years age group, AC was an independent protective factor for OS but provided no benefit for CSS.Conclusions: AC conferred age-heterogeneous survival benefits in patients with ECC, wherein the population aged 66–75 years derived the maximum benefit. In contrast, patients aged 18–65 years failed to obtain a statistically significant benefit from AC, while those aged over 75 years exhibited outcome-specific clinical benefits.